Koja Banana Plantlet Acclimatization at Various Concentrations of Foliar Fertilizer and Length of Containment - Srilestari, Rina; Suwardi, Suwardi (RSF Conference Series: Engineering and Technology, 2022)
Koja is a widely known variety of bananas but the availability of high-quality seeds has not been able to meet the market demand. This problem is overcome by using tissue culture, meanwhile, the success of the culture is largely determined by the acclimatization stage or adaptation of plants from heterotrophs to autotrophs. Therefore, this study aims to determine the interaction between the concentration of foliar fertilizer and the length of containment as well as the appropriate concentration for the growth of Koja banana plantlets. This is a field experiment carried out with a 2-factors split-plot design. The main plot was the foliar fertilizer concentration namely M1 = 2 ml/L; M2 = 4 ml/L; M3 = 6 ml/L, while the subplots were the length of containment namely E1 = 10 days; E2 = 20 days; E3 = 30 days. Based on the results, there was an interaction between the concentration of foliar fertilizer 4 mL/L and the length of containment of 20 days on the height, root volume, as well as fresh and plant dry weight.